The Bloomsbury Handbook of Student Politics and Representation in Higher Education - Klemencic, Manja (Bloomsbury Handbooks, 2024)
This open access handbook offers a unique and unprecedented global comparative account of student politics and representation in higher education. It provides a systematic and structured range of specially commissioned chapters reflecting on the history, contemporary practices and current debates on student political agency and collective action in higher education. The chapters analyse the organisational characteristics and political activities of student governments, and map opportunities for students to intervene in and influence higher education institutions and higher education policies. The handbook re-examines and further develops the existing theoretical concepts on student agency and student impact on higher education, and analytical lenses on systems of student representation and organisational models of student governments. It depicts empirical insights from 25 countries from all world regions, 4 transnational regional student federations and the Global Student Forum. The volume is unique in bringing together established scholars with a highly diverse group of current and former student leaders, specially trained and empowered to conduct research for this handbook. It offers a major contribution to the study of higher education, and politics and governance of higher education specifically. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com.